STATISTICAL ANALYSIS OF THE CASUISTRY OF A SAMPLE OF METASTATIC DISEASE IN THE SPINE - DUARTE,DAVID MARCELO (2017)
ABSTRACT Objective: The objective of this study is to present demographic data on the occurrence of spinal metastases in the service where the work was performed and to investigate the reliability of the modified Tokuhashi score in the decision making in patients with metastatic spinal cancer. Methods: We conducted a review of medical records of all cases of vertebral bone metastasis, confirmed by anatomopathological examination, from January 2009 to June 2012. Data review included demographic details, origin of the primary cancer, duration of symptoms, localization of metastases, Karnofsky performance scale and survival based on modified Tokuhashi score. We divided patients into three groups. Group A included patients with life expectancy of less than six months, group B included patients with life expectancy of between six and 12 months, and group C included patients with a life expectancy of more than 12 months. We compared the calculated survival with the current survival in the three groups with all patients followed-up to a minimum of 1 year or until death. Results: The predict survival in group A was 63.6% according to the modified Tokuhashi score, albeit group B had only 30% agreement. Conclusions: For patients in group A, the agreement rate of patient survival was better (63.4%) than that observed in patients in group B (30%). Our sample had no patient classified as group C.